The use of evaluation in the design and development of interactive medical record systems - Herbst, Abraham J (Department of Integrative Biomedical Sciences, 2018)
An explorative study was done to develop an evaluation methodology. This method can be applied during the development of interactive medical record systems in order to provide information which can be used to improve user interaction with the system. Th e evaluation methodology consists of a number of interactive sessions with potential users of the interactive medical record system. During the first two sessions the subjects are trained to use the system. During the third and last session the subjects are videotaped while they are doing a set of benchmark tasks on the system under evaluation. The video recordings are analysed to obtain performance data. This performance data consists of task timings and a list of problems experienced (errors made) by the subjects. The systems evaluated during the study were a problem-oriented manual medical record and an interactive computerized medical record. The computerized record system was specifically developed for this study. The design and subsequent improvements to this system are documented in the study.